2020
DOI: 10.1021/acs.analchem.0c02424
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Smart Nanofluidic Sensor through a Redox Reaction Strategy for High-Performance Carbon Monoxide Sensing

Abstract: Carbon monoxide (CO), an important gas signaling molecule, demonstrated various physiological and pathological functions by regulating the ion flux of biological channels. Herein, inspired by the CO-regulated K+ channel in vivo, we propose a smart CO-responsive nanosensor through the redox reaction strategy. Such nanosensor demonstrated an outstanding CO specificity and selectivity with high ion rectification (∼9) as well as excellent stability and recyclability. Therefore, these results will provide a new dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Studies have shown that oxidative stress can induce intracellular redox imbalance and biomolecular damage, leading to the occurrence of many diseases, including cancer and cardiovascular disease. 93,94 Although ROS has damaging effects, it also has positive effects. For example, photodynamic and sonodynamic therapy based on an appropriate increase in the reactive oxygen species can induce cell senescence and apoptosis, thereby showing anti-tumor functions.…”
Section: Activatable Photoacoustic Probesmentioning
confidence: 99%
“…Studies have shown that oxidative stress can induce intracellular redox imbalance and biomolecular damage, leading to the occurrence of many diseases, including cancer and cardiovascular disease. 93,94 Although ROS has damaging effects, it also has positive effects. For example, photodynamic and sonodynamic therapy based on an appropriate increase in the reactive oxygen species can induce cell senescence and apoptosis, thereby showing anti-tumor functions.…”
Section: Activatable Photoacoustic Probesmentioning
confidence: 99%
“… 25 These emerging non-invasive techniques have been widely used in antitumor research. 26 , 27 However, due to the intrinsic or obtained resistance of cancer cells on apoptosis, the effectiveness of SDT in tumor-induced induction is limited. Therefore, the other non-apoptotic cell death model has opened new treatment pathways for eliminating cancer cells and reducing the resistance brought about apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…According to the ordinances of the National Institute of Occupational Safety and Health, the lethiferous exposure concentration and endurance of CO gas is 35 ppm for endurance of 10 h and 50 ppm for endurance of 8 h [7]. Therefore, it is particularly important to monitor CO leakage in the synthesis and application of CO as fast as possible [8].…”
Section: Introductionmentioning
confidence: 99%